Genetic analysis and clinicopathological features of ALK‐rearranged renal cell carcinoma in a large series of resected Chinese renal cell carcinoma patients and literature review. Issue 1 (18th April 2017) - Yu, Wenjuan; Wang, Yuewei; Jiang, Yanxia; Zhang, Wei; Li, Yujun
Abstract : Aims: Anaplastic lymphoma kinase ( ALK )‐rearranged renal cell carcinoma (RCC) is a rare subtype of RCC reported in recent years, with eight cases so far. The aims of the present study were to screen ALK ‐rearranged cases from a large cohort of RCCs in China to determine the frequency of ALK rearrangement and investigate the clinicopathological features and outcomes. Methods and results: Tissues from a total of 477 RCC patients in China were embedded into tissue microarrays for immunostaining. Fluorescence in‐situ hybridization (FISH) and fluorescence quantitative reverse transcription polymerase chain reaction (RT‐PCR) were applied to identify and confirm the rearrangement of ALK, and to identify the genes fused with ALK . ALK expression was identified in two of 477 RCCs. By FISH analysis, the two tumours showed either a 1R1G1F or a 2R2G signal pattern, indicating rearrangement involving ALK . Fluorescence quantitative RT‐PCR detected the TPM3–ALK fusion and EML4–ALK fusion transcripts in the two tumours, respectively. Follow‐up data were analyzed for the two cases and eight other ALK‐ rearranged RCCs reported in the literature. Two patients died from RCCs, on the 16th month and 48th month after surgery, respectively. The 5‐year cancer‐specific survival rate of patients with the 10 ALK ‐rearranged RCCs was lower than that of patients with International Society of Urological Pathology (ISUP) G1, G2 and G3 clear cell RCC (CCRCC) and papillary RCC (PRCC), but higher than that of patients with G4 CCRCC and PRCC. Conclusions: ALK ‐rearranged RCC is a rare subtype of adult RCC and is associated with distinct histological features and a poor prognosis. Identification of ALK ‐rearranged RCC has important clinical significance, because patients might benefit from ALK inhibitor therapy as used in lung adenocarcinoma.